Randomized Trial of Antibiotics in Addition to Tocolytic Therapy to Treat Preterm Labor. Issue 5 (1994) - Watts, D. Heather; Krohn, Marijane A.; Hillier, Sharon L.; Eschenbach, David A.
Abstract : Objective: The objective of this study was to assess whether antibiotic therapy plus tocolysis given to women in preterm labor would prolong pregnancy compared with tocolysis alone. Methods: A randomized, double-blind trial of intravenous mezlocillin and oral erythromycin therapy vs. placebo was used in addition to tocolysis among women in preterm labor ≤34 weeks gestation with intact membranes. Amniocentesis was performed, and chorioamnionic membranes were examined histologically and cultured for microorganisms after delivery. Results: Clinical characteristics including gestational age at enrollment, frequency of contractions, cervical Bishop's score, and white blood cell count on admission were similar in the 2 groups. Antibiotic therapy was well tolerated. No significant differences in the interval to delivery, birth weight, and neonatal outcomes were observed between the 2 groups. Women in the antibiotic group had a significantly lower incidence of postpartum infections compared with women in the placebo group. Patients with evidence of upper genital tract infection in either group had a significantly shorter interval to delivery, lower gestational age at delivery, lower mean birth weight, and increased neonatal hospitalization time. Conclusions: Lack of an antibiotic effect on the gestational age at delivery may be due to the low prevalence of upper genital tract infection among unselected women in preterm labor, to advanced preterm labor unresponsive to antibiotic therapy, or to an inability of antibiotics given alone to inhibit the cytokine response. Further work is needed to identify markers of upper genital tract infection among women in preterm labor and to evaluate other potential therapeutic interventions.